Opportunities and Risks of Technology Convergence in Precision Health - Ingrid Vasiliu Feltes; Carlos D. Bustamante; Evelyne Bischof; MD; PhD; Stephen J. Dennis; MS (Blockchain in Healthcare Today, 2026)
This ConV2X Decentralized Health 2026 executive roundtable explores how technology convergence impacts precision health outcomes. The dialogue focuses on the main technologies supporting precision health, the latest scientific developments, technology advancements, opportunities, and risks. It is moderated by BHTY journal editor Prof. Dr. Vasiliu-Feltes. Participants emphasize the latest scientific developments, opportunities, and risks associated with precision health, enabled by converging advanced technologies.